2017
DOI: 10.1177/0885328216687663
|View full text |Cite
|
Sign up to set email alerts
|

A novel human-like collagen hemostatic sponge with uniform morphology, good biodegradability and biocompatibility

Abstract: Biodegradable sponges, as a promising hemostatic biomaterial, has been clinically required over the past decades. Current hemostatic sponges are generally prepared by crosslinking and freeze-drying, but the quality control or biocompatibility is often unsatisfactory due to the freezing-caused morphological non-uniformity and the toxicity of raw materials or cross-linkers. The crosslinking often greatly retards the degradation of the sponges and thus affects the healing of the wound. In this work, we prepared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 31 publications
0
37
0
1
Order By: Relevance
“…As promising biomaterials for hemostasis, biodegradable sponges have been clinically required in the past decades [72]. GE has been extensively studied as an absorbable hemostatic material for its superior properties such as low antigenicity, good biocompatibility and biodegradability [73,74,75].…”
Section: Cs-based Composite Hemostatic Materialsmentioning
confidence: 99%
“…As promising biomaterials for hemostasis, biodegradable sponges have been clinically required in the past decades [72]. GE has been extensively studied as an absorbable hemostatic material for its superior properties such as low antigenicity, good biocompatibility and biodegradability [73,74,75].…”
Section: Cs-based Composite Hemostatic Materialsmentioning
confidence: 99%
“…in vitro enzymatic degradation analysis demonstrated that these microspheres had 40% mass loss in 4 weeks (Li et al, ). Jiang et al () synthesized biodegradable collagen sponges that demonstrated good histocompatibility in vivo, and good hemostatic effect when topically applied on bleeding liver and ear artery. However, the chitosan microspheres and collagen sponges do not have the desirable viscoelastic properties of SMP foams, which led to difficulties in delivery into deep wounds and inadequate pressure on the wounds, indicating that they are not suitable for treatment of noncompressible wounds.…”
Section: Introductionmentioning
confidence: 99%
“…This low T g range was due to the increased free volume in the amorphous polymer network, resulting from the longer branches of PCL-t compared to the traditionally used monomer polyols, N,N,N 0 ,N 0 -tetrakis(2-hydroxypropyl) ethylenediamine (HPED) and triethanolamine (TEA;Singhal et al, 2014 (Li et al, 2017). Jiang et al (2017) synthesized biodegradable collagen sponges that demonstrated good histocompatibility in vivo, and good hemostatic effect when topically applied on bleeding liver and ear artery. However, the chitosan microspheres and collagen sponges do not have the desirable viscoelastic properties of SMP foams, which led to difficulties in delivery into deep wounds and inadequate pressure on the wounds, indicating that they are not suitable for treatment of noncompressible wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible option would be introducing both drugs using a biodegradable sponge [23]. Although this method has not been specifically tested for CCH, and it will probably be more difficult to adequate such a method to CCH administration, it offers multiple possibilities, acting in the first step as a hemostatic.…”
Section: Vehiclementioning
confidence: 99%